The nutritive value of available varieties of barley straw in Lebanon. Effects of feeding barley straw of three varieties on liveweight gain in Awassi lambs - Khazaal K.; Houcheimi K.; Machlab H. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
The current experiment aimed to compare the results of nylon bag degradation of three varieties of straws with performance of animals (3 fistulated sheep). The varieties (Rihan, Pamir and Saiidi) were similar in their seed and straw production but differed in nutritive value. Three groups of Awassi lambs (mean weight 49.2 kg) were offered 250 g per head of ground barley and ad libitum straw during a 7 day adaptation period, followed by a 48 day period in which intake was recorded daily. Liveweight was recorded weekly. Daily liveweight gains differed significantly. Animal performance reflected the differences between varieties obtained with the nylon bag technique. However, the proportion of leaf to stem in the straw did not follow the same trend. Because of the importance of straw in diets for ruminants in the Lebanon and the Middle East, it is suggested that selection of new cereal varieties should take into consideration the nutritive value of the straw as well as the quantities of seed and straw they produce.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)